REPRESENTASI DALAM CERITA PIETER ELBERVELD KARYA TIO IE SOEI : SUATU KAJIAN PASCAKOLONIAL - Susanto, Dwi (Kajian Linguistik dan Sastra, 2008)
Pieter Elberveld is a story written based on the historical facts of the revolt of an Indo-German descendant against the Dutch colonial government in Batavia. The revolt got a lot responses from different writers, either local, Dutch, or Chi- nese, including Tio Ie Soei. Giving the focus on the representation, this article at- tempts to give answers, based on the postcolonial perspective, to the following questions: (1) how was the revolt represented by the author, (2) what did political identity the author have, and (3) what were textual and political strategies em- ployed in the story. In order to answer those questions, this article gives the focus on the image of the indigenous people, space structures, and text purposes in the representation framework of the postcolonial study.Â Key words: representation, Tio Ie Soei, Pieter Elberveld, and pascakolonialÂ